Sophia's war : a tale of the revolution - Medal-Winning, Newbery (USA Scholastic, 2014)
The revolutionary war in America rages, and rages New York City is newly occupied by the powerful British army. Young Sophua Calderwood's beloved soldier brother, William, is being held on a gruesome British prison ship Horrified by the atrocities she sees there, Sophia resolves to avenge his brutal treatment and help advance the patriot cause.
Contents PART ONE: 1776 PART TWO: 1780 Glossary of Eighteenth-Century Words Author's Note Bibliography
Incluye Contents
Incluye Bibliography
Keywords: WAR -- U.S.A. -- 1776 -1780; REVOLUTIONARY WAR